Enhanced therapeutic effects of all-trans retinoic acid nanostructured lipid carrier composite gel drug delivery system for alopecia areata - Lingling Zheng; Yang Du; Lulu Zhang; Fuxing Jin; Wangting Li; Xuan Zhou; Yanping Yin; Yan Weng; Dong Xu; Jingwen Wang (Journal of Nanobiotechnology)
Abstract Background Alopecia areata (AA) affects approximately 2% of the global population and causes psychological distress. All-trans retinoic acid (ATRA) has the potential to promote hair regeneration; however, its clinical use is limited by skin irritation and low targeting specificity. To address these limitations, we designed an ATRA-loaded nanostructured lipid carrier gel (ATRA-NLC-Gel) drug delivery system to enhance the therapeutic effects of ATRA in AA. Results ATRA-NLC showed a uniform nanoparticle size distribution and excellent biocompatibility. In vitro, they enhanced the uptake ability of dermal papilla cells, increased cell viability, and promoted cell proliferation by facilitating the cell cycle process. Compared to ATRA cream, ATRA-NLC-Gel significantly reduced skin irritation, prolonged residence time on the skin, and achieved a sustained and slow release of ATRA. Treatment with ATRA-NLC-Gel enhanced transdermal penetration and targeted enrichment in the hair follicle region, thereby significantly promoting hair regrowth. ATRA-NLC-Gel improved AA symptoms by upregulating CD200 and Ki-67 expression, activating the Wnt/β-catenin pathway. Conclusions ATRA-NLC-Gel enhanced the transdermal permeability and follicle-targeting efficacy of ATRA, alleviated ATRA-induced skin dryness and irritation, and effectively improved the symptoms of AA in AA model mice. ATRA-NLC-Gel offers a highly promising strategy for transdermal treatment of AA in clinical setting. Graphical Abstract